Physicochemical and Antioxidant Properties of Buckwheat Protein Isolates with Different Polyphenolic Content Modified by Limited Hydrolysis with Trypsin - Xiao-Yan Wang; Chuan-He Tang (Food Technology and Biotechnology, 2012)
Effects of limited hydrolysis with trypsin on the physicochemical and antioxidant properties of buckwheat protein isolates (BPIs) obtained with untreated and 2-propanol-extracted meal have been investigated and compared. The dephenolization treatment significantly improved the hydrolysis of BPI, which resulted in the gradual decrease in total and protein-bound polyphenolic content, but an increase in the free polyphenolic content. The hydrolysis of globulins was much easier than that of the albumins. The removal of polyphenols improved the hydrolysis of the albumin fraction. The modified BPIs with high polyphenolic content exhibited much higher DPPH radical scavenging activity and reducing power, but poorer ferrous ion chelating ability than those with low polyphenolic content. These results suggest that the limited hydrolysis is suitable for modification of the properties of buckwheat proteins.